Efektivitas Model Pembelajaran Blended Learning Dalam Pendidikan Agama Hindu Di SMP Negeri 1 Denpasar - Putri, Sari Wulandari (Jayapangus Press, 2021)
Instruction may be a exceptionally imperative got to confront future challenges. The reason of instruction is for learners to secure wide information, aptitudes, and positive states of mind that they will utilize in life, so that instruction can be said to be fruitful in the event that learners accomplish positive changes within the advancement of science. The reason of this ponder was to discover out whether the mixed learning show is successfully connected in SMP Negeri 1 Denpasar. This investigate was found at SMP Negeri 1 Denpasar. The source of this investigate information was taken from observations, meet comes about, and surveys. The information collection strategy is carried out utilizing the purposive inspecting strategy, which may be a way of deciding information based on certain criteria so that respondents who drop into three categories, to be specific VII, VIII, IX totaling 104 individuals. Based on the comes about of investigate and information discourse, it can be concluded that the method of executing the mixed learning demonstrate at SMP Negeri 1 Denpasar is isolated into two stages, to be specific online and face-to-face. The Viability of the Mixed Learning Show in Hindu Instruction Amid the Covid-19 Widespread at SMP Negeri 1 Denpasar can be said that from the 104 surveys disseminated, numerous individuals are more tolerating of the combined learning show. The comes about appeared that 81 respondents in all categories unequivocally concurred and concurred that the educative learning handle can be said to be successful. In this consider, it can be concluded that the mixed learning show was successfully connected at SMPN 1 Denpasar amid the Covid-19 widespread.